Prevalence of Ocular Abnormalities in Term Infants - Hatice Daldal; Mustafa Türkyılmaz; Oğuzhan Salış; Musa Yiğit; Mustafa Muhterem Ekim (Galenos Publishing House, 2021)
Objective: To exhibit the results of routine ophthalmologic screening in infants between 0-1 years of age referred to the ophthalmology clinic from the departments of pediatrics and family medicine. Method: Referred to the ophthalmology clinic between August 2014 and November 2019, 11196 eyes of 5598 term infants were retrospectively investigated in the study, and all participants were ophthalmologically examined at 1st, 6th, and 12th months of age. Infants' pupils were dilated with 0.5% tropicamide and 2.5% phenylephrine. On examination, eye and face symmetries were evaluated with inspection, fixation, and ocular tracking. Pupil responses and motility were evaluated with the light source. While the red reflex test was evaluated using a direct ophthalmoscope, fundus was assessed through an indirect ophthalmoscope. Results: Congenital cataract (6), congenital glaucoma (3), strabismus (81), epiphora (426), non-specific retinal hemorrhages (42) and retinal pigmentation changes (10), coloboma (4) (one eyelid, four iris, one optical disc and three chorioretinal), optic disc abnormalities (3), congenital ptosis (13) (unilateral in 12 patients and bilateral in one patient), corneal dysgenesis (2) and microphthalmia (3) were determined in 11196 eyes of 5598 infants (2709 females, 2889 males). Conclusion: Perinatal ophthalmologic screening program is likely to diagnose several diseases earlier, such as congenital cataracts, congenital glaucoma, strabismus, corneal opacities, causing vision losses in infants. Treatment options are available, and some diseases can be treated due to early intervention. Early treatment can also eliminate the problems precluding the development of complex visual ability continuing in perinatal period. Consequently, final visual acuity may be increased.